Profil Kursus Menjahit pada Lembaga Kursus dan Pelatihan (LKP) Ganesha - Eka Prasetyaningsih; Hapsari Kusumarwardani; Nur Endah Purwaningsih (Universitas Ngeri Malang, 2021)
The purpose of this study is to obtain information about the profile of the sewing course program at LKP Ganesha. This research uses descriptive method with a qualitative approach. Data collection techniques are carried out using observation, interviews, and documentation. The results of the study are: 1) the establishment and development of sewing courses in LKP Ganesha has been through administrative and technical licensing processes, there are four levels of sewing courses and the funding for courses are determined by the level 2) personnel management which includes organizational structure accompanied by clear task division, but the academic qualifications for course instructors are not yet in line with standards, 3) course period are done in three months and the learning materials are in accordance with Course Curriculum Level II and III of Fashion Training, LKP Ganesha does not yet have a structured education calendar and the standardized learning time has not yet reached the minimum standard of course time, 4) learning infrastructure for sewing courses provided are in accordance with the standards set out in the Act, while the learning facilities provided do not meet the established standards, 5) LKP Ganesha cooperates with 11 government, 3 schools and 6 fashion industries, collaborative activities carried out are training providence, licensing related to course programs, institutions quality improvements, and labor distribution. This research is expected to be a reference material for readers who have an interest in establishing educational institutions in the field of clothing and can be used as material for the development of course institutions in the future. Tujuan dari penelitian ini yaitu untuk mendapatkan informasi mengenai profil program kursus menjahit di LKP Ganesha. Metode penelitian ini adalah deskriptif dengan pendekatan kualitatif. Teknik pengumpulan data dilakukan menggunakan observasi, wawancara serta dokumentasi. Hasil penelitian yaitu: 1) pendirian dan pengembangan program kursus menjahit di LKP Ganesha melalui proses perijinan administratif dan teknis, terdapat empat level kursus menjahit dengan pembiayaan kursus yang disesuaikan dengan level 2) manajemen personalia yang meliputi struktur organisasi disertai dengan pembagian tugas yang jelas, akan tetapi kualifikasi akademik bagi instruktor belum sesuai dengan standar, 3) kegiatan pembelajaran dilakukan dalam tiga bulan dan materi pembelajarannya berpedoman pada Kurikulum Kursus dan Pelatihan Tata Busana jenjang II dan III berbasis KKNI, LKP Ganesha belum memiliki kalender pendidikan yang terstruktur dan standar waktu belajar belum mencapai standar minimal waktu kursus, 4) prasarana pembelajaran kursus menjahit yang tersedia sesuai dengan standar yang diatur dalam UU, sedangkan sarana pembelajaran yang disediakan belum memenuhi standar yang ditetapkan, 5) LKP Ganesha menjalin kerjasama dengan 11 instansi pemerintah, 3 sekolah dan 6 industri busana, kegiatan kerjasama yang dilakukan yaitu pengadaaan pelatihan, perijinan program kursus, peningkatan mutu lembaga, serta penyaluran tenaga kerja. Penelitian ini diharapkan dapat menjadi bahan rujukan bagi pembaca yang memiliki minat untuk mendirikan lembaga pendidikan di bidang busana, serta dapat menjadi bahan untuk pengembangan lembaga kursus di masa yang akan datang.